Students’ Perspectives on Influencer Endorsements in Marketing Local G2G Skincare Products on Instagram - Dalimunthe, Nur Samaniatun; Sazali, Hasan (Ali Institute of Research and Publication, 2026)
This study aims to analyze students’ perspectives on influencer endorsement in the marketing of local G2G skincare products on Instagram. The increasing use of influencers in digital marketing strategies reflects a shift in marketing communication patterns; however, limited studies have specifically examined how students, as consumers, interpret influencer endorsement in the context of local products. This research employs a qualitative descriptive approach, with data collected through in-depth interviews with students of Universitas Islam Negeri Sumatera Utara who actively use social media. The findings indicate that influencer endorsement is perceived as a factor influencing interest and trust in products, particularly when influencers are considered credible, relevant to the product, and demonstrate authentic usage experiences. However, students do not passively accept endorsement content; instead, they engage in critical evaluation of the information presented. Furthermore, trust in the product is influenced not only by influencers but also by personal experience, peer reviews, and brand reputation. This study highlights that the effectiveness of influencer endorsement in marketing local skincare products depends not merely on influencer popularity, but on perceived credibility and relevance from the consumers’ perspective.